Primary squamous cell carcinoma at ileostomy site. Two case reports and review of literature. Issue 8 (27th May 2020) - Bani Hani, Murad; Butler, Bryan; Leberer, Daniel; Attuwaybi, Bashir
Abstract: SCC at ileostomy is rare, early diagnosis by sampling abnormal tissue around ileostomy is vital. Abstract : SCC at ileostomy is rare, early diagnosis by sampling abnormal tissue around ileostomy is vital.